The Cape government's rule of Basutoland, 1871-1883 - Bradlow, Edna (Department of Historical Studies, 2019)
In studying the Cape Government’s rule in Basutoland certain complementary themes arise, which though they are all germane to the problem, have had to be handled very briefly. The two main protagonists were the Cape Government and the Basuto. At the time of the annexation the Cape was on the eve of Responsible Government and all the burdens this entailed, the Basuto, after several years close, though uneasy, contact with the Free State burghers on their Western boundary, were proving themselves adept at learning the external features of a different civilization while still aligning tenaciously to traditional ideas and forms. Watching over these two major participants was the British Colonial Office, balancing, often precariously, between two opposite policies – a desire to be rid of the expense of colonial administration and a fear of abandoning the British colonies, especially in South Africa, to a state of confusion.